A 1200MPa grade ultra-high strength high plasticity steel and its preparation method

By accurately controlling element ratio and process technology, a specific microstructure is formed, which solves the problem of degradation of plasticity of existing ultra-high strength steels, and achieves the effects of ultra-high strength, high plasticity and excellent low-temperature toughness.

CN119776740APending Publication Date: 2025-04-08CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411821243.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

When the strength of existing ultra-high strength steel reaches the 1100MPa level, the plasticity decreases significantly, and the elongation is generally less than 15%, making it difficult to improve strength and plasticity at the same time.

Method used

By precisely controlling the types and content of elements, especially the elemental ratio of Al, Ni, and Cu, combined with two-stage rolling, air-cooling and two-tempering + tempering processes, tempered martensite, ferrite and reverse transformed austenite, as well as Ni3Al precipitation phase and Cu precipitation particles.

Benefits of technology

The steel has achieved ultra-high strength, high plasticity, excellent low-temperature toughness, yield strength ≥1200MPa, tensile strength ≥1300MPa, elongation ≥20.0%, impact work ≥80J in -40℃, and strong plastic accumulation is above 26000MPa·%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776740A_ABST
    Figure CN119776740A_ABST
Patent Text Reader

Abstract

The present invention relates to a 1200MPa ultra-high strength high plasticity steel and a preparation method thereof, and belongs to the technical field of ultra-high strength steel. The chemical composition of the 1200MPa ultra-high strength high plasticity steel is calculated by mass percentage as follows: C: 0.08%-0.12%, Si: 0.10%-0.25%, Mn: 1.0%-2.0%, Ni: 9.5%-10.5%, Cr: 0.8%-1.2%, Ti: 0.008%-0.015%, Mo: 0.85%-1.2%, V: 0.085%-0.15%, Als: 0.6%-0.8%, Cu: 1.0%-2.0%, 0<N≤0.004%, P≤0.005%, S≤0.005%, and the rest are Fe and unavoidable impurity elements; Ni=0.155-10Als+Cu. The steel of the present invention has the characteristics of ultra-high strength, high plasticity, excellent low-temperature toughness and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultra-high strength steel, and in particular to a 1200MPa ultra-high strength high plasticity steel and a preparation method thereof. Background Art

[0002] When the strength of existing ultra-high strength steel reaches 1100MPa, the plasticity of ultra-high strength steel decreases significantly, and the elongation is generally less than 15%. Improving the strength and plasticity of ultra-high strength steel at the same time has long been a major theoretical problem in the field of ultra-high strength steel research and development, and is also a bottleneck from basic research to technological innovation and application practice. Summary of the invention

[0003] In view of the above analysis, the present invention aims to provide a 1200MPa grade ultra-high strength and high plasticity steel and a preparation method thereof, so as to solve the problem of low elongation and strength-plasticity product of existing ultra-high strength steel.

[0004] The purpose of the present invention is mainly achieved through the following technical solutions:

[0005] The invention provides a 1200MPa ultra-high strength and high plasticity steel. The chemical composition of the 1200MPa ultra-high strength and high plasticity steel is as follows by mass percentage: C: 0.08%-0.12%, Si: 0.10%-0.25%, Mn: 1.0%-2.0%, Ni: 9.5%-10.5%, Cr: 0.8%-1.2%, Ti: 0.008%-0.015%, Mo: 0.85%-1.2%, V: 0.085%-0.15%, Als: 0.6%-0.8%, Cu: 1.0%-2.0%, 0<N≤0.004%, P≤0.005%, S≤0.005%, and the rest are Fe and unavoidable impurity elements;

[0006] Ni=0.155-10Als+Cu, wherein Ni, Als and Cu represent the mass percentages of the corresponding elements.

[0007] Furthermore, the chemical composition of 1200MPa grade ultra-high strength and high plasticity steel is as follows by mass percentage: C: 0.08%~0.11%, Si: 0.10%~0.24%, Mn: 1.0%~1.5%, Ni: 9.6%~10.5%, Cr: 0.9%~1.2%, Ti: 0.008%~0.014%, Mo: 0.9%~1.2%, V: 0.09%~0.15%, Als: 0.65%~0.8%, Cu: 1.1%~1.9%, N: 0.002%~0.004%, P≤0.005%, S≤0.005%, and the rest are Fe and unavoidable impurity elements.

[0008] Furthermore, the microstructure of the 1200MPa grade ultra-high strength and high plasticity steel includes tempered martensite, ferrite and reversed austenite, as well as Ni3Al precipitation phase and Cu precipitation particles.

[0009] The present invention also provides a method for preparing 1200MPa ultra-high strength and high plasticity steel, which is used to prepare the above-mentioned 1200MPa ultra-high strength and high plasticity steel, and the preparation method comprises:

[0010] Step 1: molten iron pretreatment;

[0011] Step 2: converter smelting;

[0012] Step 3: LF refining;

[0013] Step 4: RH refining;

[0014] Step 5: Continuously casting to obtain a continuous casting billet;

[0015] Step 6: heating the continuous casting billet, and performing controlled rolling and controlled cooling on the continuous casting billet;

[0016] Step 7: Offline quenching and tempering: The continuous casting billet after controlled rolling and controlled cooling is subjected to offline quenching and tempering to obtain 1200MPa grade ultra-high strength and high plasticity steel.

[0017] Furthermore, in step 7, the offline tempering includes two quenching processes and one tempering process.

[0018] Furthermore, in step 7, the heating temperature of the primary quenching process is 760-790°C.

[0019] Furthermore, in step 7, the heating temperature of the secondary quenching process is 620-650°C.

[0020] Furthermore, in step 7, the heating temperature of the tempering process is 560-580°C.

[0021] Furthermore, in step 6, controlled rolling and controlled cooling adopt two-stage rolling, the first stage rolling is rough rolling, and the final rolling temperature is ≥950°C.

[0022] Furthermore, in step 6, the final rolling temperature of the second stage rolling is below 850°C.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0024] 1. The present invention ensures excellent mechanical properties of steel by precisely controlling the types and contents of elements, especially the element ratio of Al, Ni and Cu, and achieves ultra-high strength, high plasticity and excellent low-temperature toughness of steel.

[0025] 2. The preparation method of the present invention combines two-stage rolling, air cooling and two quenching + tempering processes to ensure that the microstructure of the steel includes tempered martensite, ferrite and reversed austenite, as well as Ni3Al precipitation phase and Cu precipitation particles, the volume percentage of tempered martensite is not less than 70%, the volume percentage of ferrite is not less than 15%, and the volume percentage of reversed austenite is not less than 10%. The excellent comprehensive mechanical properties of the steel are ensured. The production process of the preparation method of the present invention is simple and can be applied on a large scale.

[0026] 3. The yield strength of the ultra-high strength steel of the present invention is ≥1200MPa (e.g. 1230-1260MPa), the tensile strength is ≥1300MPa (e.g. 1310-1330MPa), the elongation is ≥20.0% (e.g. 20%-22%), the impact energy at -40°C is ≥80J (e.g. 100-120J), and the strength-plasticity product is 26000MPa·% or more (e.g. 26200-27800MPa·%). The steel of the present invention has the characteristics of ultra-high strength, high plasticity, excellent low-temperature toughness, etc.

[0027] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0029] Figure 1 It is the EBSD structure of 1# steel of the present invention;

[0030] Figure 2 These are the Ni3Al precipitation phase and Cu precipitation particles of No. 1 steel of the present invention. DETAILED DESCRIPTION

[0031] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.

[0032] At present, the elongation of ultra-high strength steel above 1100MPa is low, which cannot fully meet the application requirements of ships and marine engineering equipment for ultra-high strength and high plasticity steel. The inventors conducted in-depth research to solve the problem that the elongation of existing ultra-high strength steel is less than 15%.

[0033] The invention provides a 1200MPa ultra-high strength and high plasticity steel. The chemical composition of the 1200MPa ultra-high strength and high plasticity steel is calculated by mass percentage as follows: C: 0.08%-0.12%, Si: 0.10%-0.25%, Mn: 1.0%-2.0%, Ni: 9.5%-10.5%, Cr: 0.8%-1.2%, Ti: 0.008%-0.015%, Mo: 0.85%-1.2%, V: 0.085%-0.15%, Als: 0.6%-0.8%, Cu: 1.0%-2.0%, 0<N≤0.004%, P≤0.005%, S≤0.005%, and the rest are Fe and unavoidable impurity elements.

[0034] Specifically, in the chemical composition of the above-mentioned 1200MPa-grade ultra-high strength and high plasticity steel, Ni=0.155-10Als+Cu, where Ni, Als, and Cu represent the mass percentages of the corresponding elements. The yield strength of steel can be improved by using nano-scale Ni3Al and Cu precipitation phases, where the Ni3Al nano-coherent phase consumes a certain amount of Ni element and reduces the contribution of Ni to low-temperature toughness. At the same time, Ni element needs to be added in a 1:1 ratio to reduce the effect of Cu on hot cracking of steel plates. Therefore, the content of Ni added to the steel needs to consider the effects of Ni3Al precipitation phase and Cu precipitation phase. After in-depth research, the content of Ni, Als, and Cu is controlled to meet the above relationship.

[0035] The effects and dosages of the chemical components in the present invention are described in detail below, and only % is used to represent the mass percentage in the composition.

[0036] C: The C content needs to be below 0.12% to ensure the toughness and plasticity of the steel plate; when the C content is less than 0.08%, it will not meet the requirements of ultra-high strength. Therefore, the C content is controlled at 0.08% to 0.12%.

[0037] Mn: Mn solid solution in steel will increase the strength of the steel. The Mn content should be controlled above 1.0% to ensure the strength of the steel. When the Mn content exceeds 2.0%, center segregation will occur, reducing the low-temperature toughness of the parent material. Therefore, the Mn content is controlled at 1.0% to 2.0%.

[0038] Si: Si is usually used as a deoxidizer in steelmaking. When the silicon content is less than 0.1%, the molten steel is easily oxidized. Si is also a solid solution strengthening element, but a large amount of Si is usually unfavorable to welding performance. In order to ensure the toughness of the welding heat affected zone, the Si content should be controlled below 0.25%. Therefore, the Si content is controlled at 0.1% to 0.25%.

[0039] Als: Als is an important strengthening element. When the Als content is less than 0.6%, it is difficult to play the role of Ni3Al phase precipitation strengthening. When the Als content is too high, coarse Al oxide inclusions will be formed and aggregated into clusters, becoming crack sources and causing a decrease in toughness. Therefore, the Als content should be controlled at ≥0.6%, for example, the Als content should be controlled at 0.6% to 0.8%.

[0040] Ni: Ni can improve the low temperature toughness of the material and combine with Al to form Ni3Al strengthening phase. In order to improve the low temperature toughness requirements of ultra-high strength steel, it is necessary to add a certain amount of Ni element to improve the low temperature toughness and precipitation strengthening effect of the steel plate. However, too high Ni content will increase Ceq and Pcm, causing the preheating temperature of the steel plate to be too high, so the Ni content cannot be higher than 10.5%. Therefore, the Ni content is controlled at 9.5% to 10.5%.

[0041] V: V element usually acts through solute drag and precipitation particles (V(C,N)). On the one hand, it pins the original austenite grain boundary during the material deformation process, and on the other hand, precipitation strengthening improves the strength of the material. The V content is controlled at 0.085% to 0.15%.

[0042] Cr: Cr can improve the hardenability of the material and can increase the strength of the material in the form of carbides. If the Cr content is lower than 0.8%, it is difficult to play its role. However, if the Cr content exceeds 1.2%, it will reduce the low-temperature toughness of the base material and the welding heat-affected zone, and increase the manufacturing cost of the material. Therefore, Cr is controlled at 0.8% to 1.2%.

[0043] Mo: Mo can improve the hardenability of materials, promote low-temperature microstructure transformation, and improve the strength of materials. If the Mo content is less than 0.85%, the effect of Mo is low. If the Mo content exceeds 1.2%, it not only increases the manufacturing cost, but also damages the weldability of the steel plate. Therefore, Mo is controlled at 0.85% to 1.2%.

[0044] Cu: Cu and Ni elements are usually added in combination. The use of Cu aging precipitation particles can improve the strength of high-strength steel plates, promote the uniform dispersion of Ni3Al phases, and compensate for the strength reduction caused by ultra-low carbon. However, excessive Cu elements will increase the carbon equivalent (Ceq) and cold crack sensitivity index (Pcm), causing the preheating temperature of the material to increase during welding. Therefore, the Cu content is controlled at 1.0% to 2.0%.

[0045] Ti: Ti combines with N to form TiN, which inhibits the growth of austenite grains during the heating process of the continuous casting billet and pins the austenite grain size during the welding thermal cycle, thereby improving the toughness of the steel plate and the welding heat affected zone. When the Ti content is lower than 0.01%, it is not easy to play the above role; excessive Ti reduces the precipitation time of TiN and increases the temperature, reducing the pinning effect on austenite grains. Therefore, the Ti content is controlled at 0.008% to 0.015%.

[0046] P: Phosphorus is an impurity element in steel, which will damage the toughness of the steel plate and the heat-affected zone of welding. Therefore, the P content is controlled below 0.005%.

[0047] S: Sulfur is an impurity element in steel, which will form sulfide inclusions and become a crack source. Therefore, the S content is controlled below 0.005%.

[0048] N: A certain amount of N can form Ti(C,N) with Ti, improve the toughness of the steel plate and the heat-affected zone of welding, and form carbonitrides with Ti to improve strength; but too high a N content will affect the low-temperature toughness of the material. Therefore, the N content is controlled at 0<N≤0.004%.

[0049] Specifically, in order to further improve the comprehensive performance of the above-mentioned 1200MPa grade ultra-high strength and high plasticity steel, the chemical composition of the above-mentioned 1200MPa grade ultra-high strength and high plasticity steel is calculated by mass percentage: C: 0.08%~0.11%, Si: 0.10%~0.24%, Mn: 1.0%~1.5%, Ni: 9.6%~10.5%, Cr: 0.9%~1.2%, Ti: 0.008%~0.014%, Mo: 0.9%~1.2%, V: 0.09%~0.15%, Als: 0.65%~0.8%, Cu: 1.1%~1.9%, N: 0.002%~0.004%, P≤0.005%, S≤0.005%, and the rest are Fe and unavoidable impurity elements.

[0050] The present invention also provides a method for preparing the above-mentioned 1200MPa grade ultra-high strength and high plasticity steel, comprising the following steps:

[0051] Step 1: molten iron pretreatment;

[0052] Step 2: converter smelting;

[0053] Step 3: LF refining;

[0054] Step 4: RH refining;

[0055] Step 5: Continuously casting to obtain a continuous casting billet;

[0056] Step 6: heating the continuous casting billet, and performing controlled rolling and controlled cooling on the continuous casting billet;

[0057] Step 7: Offline quenching and tempering: The continuous casting billet after controlled rolling and controlled cooling is subjected to offline quenching and tempering to obtain 1200MPa grade ultra-high strength and high plasticity steel.

[0058] Specifically, in the above step 1, the impurity elements in the steel are reduced by pretreatment of the molten iron to ensure that after KR desulfurization, the S content is ≤ 0.007% and the slag thickness meets the slag removal level 1.

[0059] Specifically, in the above step 2, during converter smelting, the slag layer thickness is required to be ≤100mm when slag blocking and steel tapping, the added alloy material and auxiliary materials such as lime, sintered ore, dolomite, etc. must be dry, and the order of alloying and deoxidation of the ladle is from strong to weak.

[0060] Specifically, in the above step 3, during the LF refining process, the added slag-making materials and deoxidizers must be dried and kept in the silo for ≤24 hours to ensure that the slag has good fluidity; the white slag holding time is ≥10 minutes, and Ti and Fe must be added after deoxidation is complete.

[0061] Specifically, in the above step 4, during the RH refining process, calcium treatment is performed before steel tapping, and the static argon blowing time after wire feeding is ≥10 minutes to ensure that the Ca content in the molten steel is 0.001% to 0.0015%.

[0062] Specifically, in the above step 5, the continuous casting process adopts full-process protected casting, electromagnetic stirring and light pressing, the superheat of the tundish is ≤35°C, and after continuous casting, it enters the slow cooling pit for treatment to obtain a continuously cast billet.

[0063] Specifically, in the above step 5, the thickness ratio of the continuous casting billet to the finally obtained 1200 MPa grade ultra-high strength and high plasticity steel is controlled to be greater than 5, so as to achieve the purpose of refining the core structure of the steel plate.

[0064] Specifically, in the above step 6, the heating temperature of the continuous casting billet is ≤ 1200°C to ensure that the austenite grains do not grow. Preferably, the heating temperature of the continuous casting billet is 1150-1200°C, such as 1160°C, 1170°C, 1180°C, 1190°C.

[0065] Specifically, in step 6, the controlled rolling and controlled cooling adopts a two-stage rolling method: divided into a first stage rolling and a second stage rolling, so as to give full play to the effect of the controlled rolling and controlled cooling process on refining the grain size of the material.

[0066] Specifically, in the above step 6, the first stage rolling is rough rolling, and the first stage rolling is a rapid deformation in the austenite recrystallization temperature range; considering that the final rolling temperature of the first stage rolling is too high, it is not conducive to the rolling process design, and too small austenite cannot be fully refined in the high temperature stage. Therefore, the final rolling temperature of the first stage rolling is controlled to be ≥950°C, such as 950°C to 1040°C, such as 960°C, 970°C, 980°C, 990°C, 1000°C, 1010°C, 1020°C, 1030°C.

[0067] Specifically, in the above step 6, considering that the single-pass deformation of the first stage rolling is too large, resulting in a significant increase in the torque of the rolling mill, and too small a deformation cannot reach the critical deformation for dynamic recrystallization of austenite. Therefore, the single-pass deformation is controlled to be 10% to 25%, for example, 10% to 18%.

[0068] Specifically, in the above step 6, considering that if the cumulative deformation of the first stage rolling is too large, the cumulative deformation of the finishing stage will be reduced, and if it is too small, the austenite grains cannot undergo dynamic recrystallization. Therefore, the cumulative deformation of the first stage rolling is controlled to be ≤50%, for example, 30% to 40%.

[0069] Specifically, in the above step 6, the second stage of rolling is finishing rolling. Considering that if the start rolling temperature of finishing rolling is too high, the austenite grains will undergo static recrystallization quickly, and if it is too low, the deformation resistance will increase and the rolling process cannot be completed. Therefore, the start rolling temperature of finishing rolling is controlled to be ≤950℃, such as 900~950℃, such as 910℃, 920℃, 930℃, 940℃.

[0070] Specifically, in the above step 6, if the final rolling temperature of the finishing rolling is too high, the deformed austenite grains cannot accumulate enough deformation bands and dislocation density, and if it is too low, the torque of the rolling mill increases and the steel plate is difficult to deform. Therefore, the final rolling temperature of the finishing rolling is controlled to be below 850°C, such as 780-840°C, such as 790°C, 800°C, 810°C, 820°C, and 830°C.

[0071] Specifically, in the above step 6, in order to increase the deformation band and dislocation density, the final rolling deformation of the finishing rolling is controlled to be ≥15%, for example, 15% to 18%.

[0072] Specifically, in the above step 6, considering that the cumulative deformation of the finishing rolling is too large, the deformation in the rough rolling stage is too small to achieve austenite grain refinement in the high temperature stage, and too small is not conducive to the refinement of the final phase transformation structure. Therefore, the cumulative deformation of the finishing rolling is controlled to be ≥50%, for example, 60% to 70%.

[0073] Specifically, in step 7, the offline tempering includes two quenching processes and one tempering process.

[0074] Specifically, in step 7, if the heating temperature of the primary quenching process is too high, the austenite grains will grow, which is not conducive to the low-temperature toughness of the steel plate, and if it is too low, it will not be conducive to the homogenization of the austenite grains. Therefore, the heating temperature of the primary quenching process is controlled to be 760-790°C, and the holding time is 1-2h.

[0075] Specifically, in step 7, the heating temperature of the secondary quenching process is too high, resulting in too high secondary martensite content, and although the strength increases, the toughness decreases. If it is too low, the secondary martensite content is insufficient and the strength cannot reach 1200MPa. Therefore, the secondary quenching temperature is controlled to be 620-650°C, and the holding time is 1-2h.

[0076] Specifically, in step 7, the heating temperature of the tempering process is too high, resulting in dislocation recovery and coarsening of the precipitate phase of the steel plate, which reduces the strength. If the heating temperature is too low, the strength of the steel plate is too high and the toughness is insufficient. Therefore, the heating temperature of the tempering process is controlled to be 560-580°C, the holding time is 1-2h, and the steel plate is cooled to room temperature after the holding time.

[0077] It should be noted that the content of Al, Ni and Cu is the most important element affecting the strength, plasticity and low temperature performance in the present invention. In combination with the process of the present invention, a certain proportion of reverse austenite can be formed to achieve plasticization; since the introduction of the soft phase "reverse austenite" and the ferrite phase leads to a decrease in strength, the composition design of the present invention utilizes Ni3Al precipitation to compensate for the strength loss.

[0078] The microstructure of the steel of the present invention includes tempered martensite, ferrite and reversed austenite, as well as Ni3Al precipitated phase and Cu precipitated particles, wherein the volume percentage of tempered martensite is not less than 70%, the volume percentage of ferrite is not less than 15%, and the volume percentage of reversed austenite is not less than 10%. For example, the volume percentage of tempered martensite is 70% to 75%, the volume percentage of ferrite is 15% to 18%, and the volume percentage of reversed austenite is 11% to 15%.

[0079] Specifically, the volume percentage of the Ni3Al precipitated phase is about 0.1% to 0.5%, and the volume percentage of the Cu precipitated particles is about 0.1% to 0.5%.

[0080] The yield strength of the ultra-high strength steel of the present invention is ≥1200MPa (for example, 1230-1260MPa), the tensile strength is ≥1300MPa (for example, 1310-1330MPa), the elongation is ≥20.0% (for example, 20%-22%), the impact energy at -40°C is ≥80J (for example, 100-120J), and the strength-plasticity product is above 26000MPa·% (for example, 26200-27800MPa·%); the steel of the present invention has the characteristics of ultra-high strength, high plasticity, excellent low-temperature toughness, etc., and is used to solve the problem that the elongation of the existing ultra-high strength steel is lower than 15%.

[0081] The steel of the present invention can be used for large-scale ship structures or marine engineering equipment with high plasticity requirements.

[0082] The advantages of the precise control of the chemical composition, content and preparation process parameters of the present invention will be demonstrated below with specific examples and comparative examples.

[0083] Example

[0084] This embodiment discloses three types (1#-3# steels) of 1200MPa grade ultra-high strength and high plasticity steels and preparation methods thereof.

[0085] The preparation method of 1#-3# steel includes the following steps:

[0086] (1) Hot metal pretreatment: Hot metal S≤0.008%;

[0087] (2) Converter smelting: slag layer thickness ≤ 100 mm;

[0088] (3) LF refining: standby time in the silo ≤ 24 hours; white slag retention time ≥ 10 minutes, Ti and Fe are added after deoxidation is complete;

[0089] (4) RH refining: Calcium treatment is carried out before steel is tapped, and the static argon blowing time after wire feeding is ≥10 min to ensure that the Ca content in the molten steel is 0.001% to 0.0015%;

[0090] (5) Continuous casting: The target superheat of the molten steel in the tundish is ≤35°C, and after continuous casting, it enters the slow cooling pit for treatment; the thickness ratio of the continuous casting billet to the final 1200MPa grade ultra-high strength and high plasticity steel is controlled to be greater than 5;

[0091] (6) Controlled rolling and controlled cooling: the reheating temperature of the continuous casting billet is ≤1200℃; two-stage rolling, the first stage (rough rolling) is rolling for rapid deformation in the austenite recrystallization temperature range, the final rolling temperature is ≥950℃, the single-pass deformation is 10-15%, and the cumulative deformation of the first stage rolling is ≤50%; the second stage rolling is finishing rolling, the starting rolling temperature is ≤950℃, the final rolling temperature is not higher than 850℃, the final rolling deformation is ≥15%, and the cumulative deformation of the second stage rolling is ≥50%;

[0092] (7) Offline quenching and tempering: primary quenching process: heating temperature 760-790°C, holding time 2h; secondary quenching process: 620-650°C, holding time 1-2h; tempering process: 560-580°C, holding time 1-2h.

[0093] The thickness ratio of the continuous casting billet to the final 1200MPa grade ultra-high strength and high plasticity steel is greater than 5.

[0094] The inventors conducted a large number of experimental studies during the research process, using some solutions with poor performance (4#, 5#) as comparison steels.

[0095] The chemical composition of 1#~5# steel is shown in Table 1, the specific process parameters of the preparation method are shown in Table 2; the microstructure is shown in Table 3, and the mechanical properties test results are shown in Table 4.

[0096] The microstructure of 1# steel is shown in Figure 1 As shown in Figure 1, the Ni3Al precipitated phase and Cu precipitated particles of steel 1 are as follows: Figure 2 shown.

[0097] Table 1 Chemical composition of 1#-5# steel (wt, %)

[0098]

[0099] Table 2 Process parameters of 1#-5# steel

[0100]

[0101] Table 3 Microstructure of 1#-5# steel

[0102]

[0103]

[0104] Table 4 Mechanical properties of 1#-5# steel

[0105]

[0106] In Table 3, since the amount of Ni3Al precipitated phase and Cu precipitated particles is small, the Ni3Al precipitated phase and Cu precipitated particles are not included in the calculation of the organizational content, that is, the sum of the contents of tempered martensite, ferrite and reversed austenite is 100%.

[0107] By comparison, it can be seen that the smelting methods and process parameters of 1#~5# steels are the same or similar, but the mass percentages of the elemental components of 1#~3# steels and 5# steel all meet the requirements of the present invention, the mass percentages of the elemental components of 4# steel do not meet the requirements of the present invention, the mechanical properties, tempered martensite content, and ferrite content of 1#~3# meet the requirements of the present invention, the microstructure of 4# steel does not meet the requirements of the present invention, the yield strength and tensile strength do not meet the requirements of the present invention, the microstructure of 5# steel does not meet the requirements of the present invention, and the elongation does not meet the requirements of the present invention.

[0108] By comparison, it can be seen that the present invention is based on precise chemical composition and preparation method, which can ensure the realization of excellent mechanical properties of steel plates.

[0109] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A 1200MPa grade ultra-high strength high plasticity steel, characterized in that: The chemical composition of the 1200MPa grade ultra-high strength and high plasticity steel is as follows by mass percentage: C: 0.08%-0.12%, Si: 0.10%-0.25%, Mn: 1.0%-2.0%, Ni: 9.5%-10.5%, Cr: 0.8%-1.2%, Ti: 0.008%-0.015%, Mo: 0.85%-1.2%, V: 0.085%-0.15%, Als: 0.6%-0.8%, Cu: 1.0%-2.0%, 0<N≤0.004%, P≤0.005%, S≤0.005%, and the rest are Fe and unavoidable impurity elements; Ni=0.155-10Als+Cu, wherein Ni, Als and Cu represent the mass percentages of the corresponding elements.

2. The 1200MPa grade ultra-high strength and high plasticity steel according to claim 1, characterized in that: The chemical composition of the 1200MPa grade ultra-high strength and high plasticity steel is calculated by mass percentage as follows: C: 0.08%-0.11%, Si: 0.10%-0.24%, Mn: 1.0%-1.5%, Ni: 9.6%-10.5%, Cr: 0.9%-1.2%, Ti: 0.008%-0.014%, Mo: 0.9%-1.2%, V: 0.09%-0.15%, Als: 0.65%-0.8%, Cu: 1.1%-1.9%, N: 0.002%-0.004%, P≤0.005%, S≤0.005%, and the rest are Fe and unavoidable impurity elements.

3. The 1200MPa grade ultra-high strength and high plasticity steel according to claim 1 or 2, characterized in that: The microstructure of the 1200MPa grade ultra-high strength and high plasticity steel includes tempered martensite, ferrite and reverse transformed austenite, as well as Ni3Al precipitation phase and Cu precipitation particles.

4. A method for preparing 1200MPa grade ultra-high strength and high plasticity steel, characterized in that: For preparing the 1200MPa grade ultra-high strength and high plasticity steel according to any one of claims 1 to 3, the preparation method comprises: Step 1: molten iron pretreatment; Step 2: converter smelting; Step 3: LF refining; Step 4: RH refining; Step 5: Continuously casting to obtain a continuous casting billet; Step 6: heating the continuous casting billet, and performing controlled rolling and controlled cooling on the continuous casting billet; Step 7: Offline quenching and tempering: The continuous casting billet after controlled rolling and controlled cooling is subjected to offline quenching and tempering to obtain 1200MPa grade ultra-high strength and high plasticity steel.

5. The preparation method according to claim 4, characterized in that: In the step 7, the offline tempering includes two quenching processes and one tempering process.

6. The preparation method according to claim 5, characterized in that: In step 7, the heating temperature of the primary quenching process is 760-790°C.

7. The preparation method according to claim 5, characterized in that: In step 7, the heating temperature of the secondary quenching process is 620-650°C.

8. The preparation method according to claim 5, characterized in that: In step 7, the heating temperature of the tempering process is 560-580°C.

9. The preparation method according to any one of claims 4 to 7, characterized in that: In step 6, controlled rolling and controlled cooling are carried out in two stages, wherein the first stage is rough rolling and the final rolling temperature is ≥950°C.

10. The preparation method according to claim 9, characterized in that: In step 6, the final rolling temperature of the second stage rolling is below 850°C.